Study of ovarian tumors in patients sample in Missan Governorate - Hashim, Nidhal Abdullah (Al-Qadisiyah Journal of Pure Science, 2017)
This present study was performed on (40) patient of ovarian tumors in age (20-60)year to investigate the age group which more expose for ovarian tumors accident and the relation between age and tumor nature(benign or malignant). in addition to known the symptoms of disease and detection the types of benign or malignant ovarian tumors, that during period 1/11/2010 to 1/4/2011. This study show increase percent of ovarian tumors in age group (20-30)year in percentage 35% follow by age group (31- 40)year in percentage 32.5% while was age group (51-60)year lower percent 12.5%, important symptoms of disease was the accut pain in abdomen in percent 62,5% follow by abdomen swelling in percent 17.5% and gastric and intestinal disorders in percent 12.5% in addition to menstruation disorder and urinary infection but in lower percentage . Record the benign ovarian tumors 80% compared with malignant ovarian tumors 20 % in addition to correlation between age and tumor nature ,the age group (20-30)year record higher percent in benign ovarian tumors 43.7% follow by age group (31-40)year in percent 37.5% while age group (51-60)year record lower percent 3.1% in benign ovarian tumors while it record higher percent 50% in malignant ovarian tumors follow by age group (41-50)year in percent 37.5%. This study show the benign ovarian tumors types ,record benign serous cyst adenoma percent 40.6% follow by poly cystic tumor in percent 28.9% while lower percentage was luteal cyst tumor 6.25% while malignant ovarian tumors record Serous cyst carcinoma tumor 50% follow by Immature(malignant) teratoma tumor in percent 25% while type Clear cell carcinoma,cyct teratoma tumor record lower percent 12.5% in one patient for each .